Research-Based Islamic Education Curriculum Management - Aliyah, Nur; Thabrani, Abd. Muis; Rodliyah, St.; Amal, Bakhrul Khair; Samosir, Sry Lestari (Al-Hayat: Journal of Islamic Education, 2024)
This study examines the management and implementation of a research-based curriculum to understand how Islamic education can integrate contemporary scientific knowledge with traditional religious teachings. Using a qualitative approach, case study design at Madrasah Tsanawiyah (MTs) Zainul Hasan Balung, data were collected through in-depth interviews, observation, and documentation. The validity of the findings used triangulation techniques, and data analysis followed the three steps of data reduction, presentation, and conclusion/verification. The study findings indicate that the curriculum was developed through a comprehensive planning process, including needs assessment and stakeholder collaboration to align with madrasah education's vision, mission, and goals. Its implementation involved structured research activities by forming Youth Scientific Groups (KIR) and Innovative Product Groups, which provided students with hands-on experience in scientific research and inquiry. This approach effectively fostered critical thinking, problem-solving, and research skills among students. Teachers received ongoing training to guide students' research activities, ensuring effective curriculum delivery. The study also identified challenges, such as the need for adequate teacher preparation and appropriate learning materials, which were addressed through training programs and the development of research pocketbooks. The evaluation process used authentic assessments, such as portfolios and research proposals, to ensure continuous improvement and adaptation of the curriculum. Research-based curriculum management at MTs Zainul Hasan Balung shows that integrating research-oriented learning can improve Islamic education and prepare students for modern challenges while maintaining Islamic values. These findings provide valuable insights for Islamic educational institutions that want to implement research-based curricula effectively.